Diffusion Behaviors of Hydrogen Isotopes in Incoloy 800H: A First-Principles Study - Hongyu Chen; Hong Li; Chuan Li; Jianzhu Cao; Chao Fang (Science and Technology of Nuclear Installations)
Incoloy 800H is one of the main stainless steel materials used in steam generators with High Temperature Reactor Pebble-bed Modules (HTR-PM). In this study, the diffusion behaviors of hydrogen isotopes in Incoloy 800H were investigated with first-principle calculations. Numerical results reveal that the starting and ending positions of the diffusion process are the two adjacent and most stable octahedral sites surrounded by Fe atoms and Ni atoms, and the diffusion follows an indirect path via the metastable tetrahedral sites and octahedral sites surrounded by Fe atoms and Cr atoms. The diffusion activation energies of hydrogen (H), deuterium (D), and tritium (T) in Incoloy 800H are investigated by first-principles calculations with the same approximate value of Q=0.757 eV; the diffusion coefficient frequency factors are also obtained with values of D0=1.56×10-6, 1.10×10-6, and 8.99×10-7 (m2/s) for H, D, and T, respectively. Furthermore, the theoretical results are compared with the experimental data, and it is found that both are in agreement with each other. These results are very helpful for understanding the diffusion behaviors of hydrogen isotopes in Incoloy 800H and can be used to guide the tritium source term analysis of secondary circuits in HTR-PM, which are first studied from a microperspective.